An agronomic impact evaluation of the Maize-Nutrient-Manager (MNM) mobile phone application in the Southern Highlands of Tanzania - Kilakila, Mukoma Kitundu (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Fertilizer intensification is often perceived as an option for improving food security in SSA, where low inherent soil fertility and fertilizer use have led to soil mining and low yields of important staple crops such as maize. Intensifying fertilizer use in Africa may have negative impacts on the environment and might not be economically viable. Therefore, a focus on improving fertilizer use efficiency (FUE) can be an alternative that can help to minimize nutrient losses to the environment, while at the same time increasing maize grain yields. However, one major constraint in African smallholder farming systems is a lack of fertilizer recommendations that are tailored to specific farmer and field conditions. This study evaluates the agronomic impact of a field-specific fertilizer advisory tool on FUE. The Maize-Nutrient-Manager (MNM) tool is a mobile phone application that was used by extension workers advising maize-growing smallholder farmers in the Southern Highlands of Tanzania in the 2019/20 maize season. To determine the impact of MNM advice on FUE, the Agronomic Efficiency of Nitrogen (N-AE) was used as an indicator. Using telephone-based interviews, the impact of MNM was evaluated for a subset of farmers (35 control and 40 MNM intervention). Results show that MNM advice improved N-AE in this first year of field-specific advice provision (n=40), from 8.31 in the 2018/19 to 27.39 additional kg grain yield/kg N applied in 2019/20 season. Consequently, the MNM users – with less fertilizer application - reached the same maize grain yield on average as the control group. These results indicate that decision support tools on fertilizer management - right timing of top dressing fertilizers application and a balanced application rate of N and P - can contribute to improved FUE in the maize-dominated farming systems of the Southern Highlands of Tanzania. Further research may identify more management practices in the area that can improve field-specific fertilizer advisory.